2019
DOI: 10.1016/j.bpsc.2019.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in the Relationship Between Inflammation and Reward Sensitivity: A Randomized Controlled Trial of Endotoxin

Abstract: BACKGROUND: There are robust sex differences in the prevalence of depression. Inflammation and anhedonia may play a role in understanding these sex differences. Indeed, sex differences in inflammation-induced neural responses to reward may provide insight into the sex gaps in depression, but no study has examined this question. METHODS: As such, the current study examined whether there were sex differences in reward-related neural activity (i.e., ventral striatum [VS] activity) in response to an experimental i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 47 publications
2
28
0
Order By: Relevance
“…KYN increased by the 2 h time point, and by the six hour time point KYN concentrations were decreasing back toward baseline levels. This is similar to our findings regarding cytokine concentrations, which peaked at the 2 h time point following endotoxin administration (Eisenberger et al, 2010a;Inagaki et al, 2012;Moieni et al, 2019). However, changes in concentrations of KynA and Trp were largely driven by later change, occurring between the 2 h and the 6 h time points (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…KYN increased by the 2 h time point, and by the six hour time point KYN concentrations were decreasing back toward baseline levels. This is similar to our findings regarding cytokine concentrations, which peaked at the 2 h time point following endotoxin administration (Eisenberger et al, 2010a;Inagaki et al, 2012;Moieni et al, 2019). However, changes in concentrations of KynA and Trp were largely driven by later change, occurring between the 2 h and the 6 h time points (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…Our first set of findings showing that greater inflammation is associated with lower neural activity in the amygdala, hippocampus, insula and temporal pole activity in response to positive stimuli is consistent with a growing literature documenting associations between inflammation and blunted neural reactivity to positive stimuli ( Capuron et al., 2012 ; Eisenberger et al ., 2010a ; Moieni et al., 2019 ). Lower reactivity to positive images in canonical regions implicated in the detection of and attention to salient stimuli suggests that less sensitivity to positive stimuli may be linked to higher low-grade inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…These studies generally find that inflammation causes a decrease in neural activity in reward-related regions (i.e. ventral striatum) in response to monetary gain ( Eisenberger et al ., 2010a ; Capuron et al., 2012 ; Moieni et al., 2019 , c.f. Inagaki et al., 2015 ; Muscatell et al ., 2016b ).…”
mentioning
confidence: 99%
“…Detailed descriptions of study procedures have already been reported (Moieni et al, 2015a, c), but are summarized here. None of the subjective social status data in this paper have been reported on previously; however, other results from the parent study have been published (Inagaki et al, 2015; Moieni et al, 2015a,b,c, 2019; Muscatell et al, 2016; Cho et al, 2017, 2019; Irwin et al, 2019). Thus, this is a secondary analysis of these data.…”
Section: Methodsmentioning
confidence: 74%